Sinergi Pendidikan Damai dan Kebijakan Pemerintah: Studi Kasus di MAN 1 Pidie, Aceh - Aminah, Siti; Ikramatoun, Siti (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
Peace education is vital for fostering harmony and sustainable development, particularly in post-conflict areas like Aceh, Indonesia. This study explores the synergy between government policies and educational practices in implementing peace values at MAN 1 Pidie. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. Informants included school staff, teachers, and government officials. Data were analyzed using Miles and Hubermans interactive model, focusing on the translation of government policies into school practices. Six core peace values”cooperation, tolerance, mutual respect, teamwork, leadership, and recognition of rights”are integrated into MAN 1 Pidie's curriculum, extracurricular activities, and school culture. Government support through policy frameworks, teacher training, and resource provision is instrumental in sustaining these efforts. While the program has successfully fostered inclusivity and reconciliation, challenges such as resource disparities and limited teacher capacity remain. Collaborative efforts between stakeholders are essential for improving sustainability and relevance. This study highlights the importance of government-education collaboration in embedding peace values.